Peningkatan Hasil Belajar Peserta Didik pada Pendidikan Pancasila Menggunakan Model Problem Based Learning di Kelas IV SDN 10 Lambung Bukit Kota Padang (Indo-MathEdu Intellectuals Journal, 2025)
This study was motivated by the low learning outcomes of students in Pancasila Education, which were caused by teacher-centred learning that did not optimally develop students' activities and critical thinking skills. This study aimed to describe the improvement in student learning outcomes through the application of the Problem-Based Learning model in Pancasila Education for Grade IV students at SDN 10 Lambung Bukit, Padang City. This research is a classroom action research conducted in two cycles, with each cycle covering the stages of planning, implementation, observation, and reflection. The research subjects consisted of teachers and 20 fourth-grade students in the July–December semester of the 2025/2026 academic year. Data were collected through tests and non-tests in the form of teaching module observations, observations of teacher and student activities, and learning outcome tests. The results showed an increase in all aspects of assessment, namely the teaching module increased from 89.58% (B) to 95.83% (SB), teacher activities from 82.14% (B) to 96.42% (SB), student activities from 82.14% (B) to 92.85% (SB), and learning outcomes in terms of attitude, knowledge, and skills also increased significantly from cycle I to cycle II. It can be concluded that the Problem-Based Learning model is effective in improving student learning outcomes in Pancasila Education.